2008
DOI: 10.1177/0269215507080122
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially allocated clinical trial of rhythmic stabilization exercises and TENS in women with chronic low back pain

Abstract: The rhythmic stabilization programmes resulted in more gains in women with chronic low back pain regarding the present outcome variables compared with the other groups; therefore, its application in female chronic low back pain patients aged 34-46 years is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(103 citation statements)
references
References 42 publications
2
97
0
4
Order By: Relevance
“…The technique was applied 3 times a week after the training for four months. The procedure was applied to the lower limb of the athlete in the supine position, and the range of motion was reached for each diagonal, with no pain, at which time the athlete was asked to perform a maximum isometric contraction against a resistance provided by the coach at the end of the movement with alternating contractions of the agonist and antagonist muscles (Kofotolis, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The technique was applied 3 times a week after the training for four months. The procedure was applied to the lower limb of the athlete in the supine position, and the range of motion was reached for each diagonal, with no pain, at which time the athlete was asked to perform a maximum isometric contraction against a resistance provided by the coach at the end of the movement with alternating contractions of the agonist and antagonist muscles (Kofotolis, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…A number of clinical studies exist concerning the use of TENS for various types of disorders such as low back pain [19-24], Myofascial [25] and arthritic pain [26], sympathetically mediated pain [26-28], bladder incontinence, neurogenic pain [29-32], visceral pain, and postsurgical pain [15, 33, 34], chronic musculoskeletal pain [18, 35]. …”
Section: Introductionmentioning
confidence: 99%
“…All trials described complete information about frequency, pulse duration and intensity of the current, except Alizadeh et al. (Alizadeh and Ahmadizad, ) Two studies reported using conventional/high‐frequency TENS (C‐TENS; 80–100 Hz; Marchand et al., ; Cheing and Hui‐Chan, ); two studies reported using acupuncture‐like/low‐frequency TENS (A‐TENS; 2–20 Hz; Kofotolis et al., ; Facci et al., ), and three studies had both high and low‐frequency TENS groups (Deyo et al., ; Topuz et al., ; Sahin et al., ). Alizadeh et al.…”
Section: Resultsmentioning
confidence: 99%
“…used Borg verbal rating pain scale, which we considered to be similar to VAS assessment as subjects were required to rate their pain level from 0 up to 10 (Kofotolis et al., ). Eight studies in this review reported pain intensity as an outcome for TENS or IFC versus placebo or control group (Deyo et al., ; Marchand et al., ; Cheing and Hui‐Chan, ; Topuz et al., ; Kofotolis et al., ; Itoh et al., ; Facci et al., ; Sahin et al., ). No studies reported >50% or >30% pain reduction, an outcome suggested by the Cochrane guidelines (Higgins et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation